2020
DOI: 10.1186/s40560-020-00499-4
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing liberation from mechanical ventilation in coronavirus disease 2019: multicenter observational study in fifteen Italian ICUs

Abstract: Background A large proportion of patients with coronavirus disease 2019 (COVID-19) develop severe respiratory failure requiring admission to the intensive care unit (ICU) and about 80% of them need mechanical ventilation (MV). These patients show great complexity due to multiple organ involvement and a dynamic evolution over time; moreover, few information is available about the risk factors that may contribute to increase the time course of mechanical ventilation. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 52 publications
9
83
2
7
Order By: Relevance
“…However, these findings were not reproducible in the duration of mechanical ventilation. Our data partially differs from Gamberini et al ,, who demonstrated that age, SOFA score at ICU admission, PaO 2 /FiO 2 , renal and cardiovascular complications, and late-onset VAP were all independent risk factors for prolonged mechanical ventilation in patients with COVID-19 [40]. Differences found may be due to the low number of patients analyzed and different methodologies implemented.…”
Section: Discussioncontrasting
confidence: 91%
“…However, these findings were not reproducible in the duration of mechanical ventilation. Our data partially differs from Gamberini et al ,, who demonstrated that age, SOFA score at ICU admission, PaO 2 /FiO 2 , renal and cardiovascular complications, and late-onset VAP were all independent risk factors for prolonged mechanical ventilation in patients with COVID-19 [40]. Differences found may be due to the low number of patients analyzed and different methodologies implemented.…”
Section: Discussioncontrasting
confidence: 91%
“…Following publication of the original article [ 1 ], the authors identified an error in the collaborator author’s name of Elena Mosconi.…”
mentioning
confidence: 99%
“…Signaling pathways differentially activated in the transitional and AEC1 states, including TGFβ, Sox4 and TNF (1214), are plausible candidates. Although COVID-19 ARDS may be associated with worse outcomes than ARDS from other etiologies (13), we suspect that this pathology is common to severe ARDS regardless of etiology.…”
Section: Resultsmentioning
confidence: 89%
“…In its most severe form, COVID-19 manifests as the acute respiratory distress syndrome (ARDS). COVID-19 ARDS causes acute respiratory failure associated with prolonged ventilator dependence and high mortality rates (13). However, the underlying mechanism by which COVID-19 ARDS results in prolonged ventilator dependence and high mortality is unknown.…”
Section: Introductionmentioning
confidence: 99%